WEA Ramblers, 1939 (1939)
1939 1939-1945 "WEA Ramblers, 1939" [HFR0201], 1939 This leaflet advertises a guided walk organised by the Westminster and West London Workers' Educational Association. The WEA become involved in organising social and educational activities for war workers, particularly those lodging in hostels.